Paradigma Baru Sistem Kesejahteraan Pegawai; Solusi Alternatif Dan Prospek Implementasinya Di Indonesia Bagian 1 Seri Sistem Kesejahteraan Aparatur - Riyadi, Riyadi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2013)
One of the issues highlighted in the bureaucratic system in Indonesia is related to well-being A low level of well-being, often used as an excuse, why bureaucratic corruption, slower, less professional. Structuring the system of earning additional revenue needed for government employees, both at central and local levels, are in the same pattern so as to reduce the occurrence of significant differences between institutions and regions_ It will also affect the diversity ( diversity ) and disparity ( difference ) income is too high formulation of any civil servant payroll system should be based on consideration of adequate basic needs In addition other conditions of any employee ( PNS) also need to be considered. The values contained in a payroll system, particularly in the public sector, is not only meant to formulate a system that is fair and proportionate compared to the duties and responsibilities alone, but also to consider matters related to diversity as part of the income of civil servants social environment. It means that the environmental conditions concerning purchasing power and level of expensiveness, and incentive systems that exist in areas where civil servants are , should be part of the considerations in determining the formula the payroll system. Keywords: well-being system, formulation of payroll system, income, civil servants, civil servants